PRIMARY PCI FOR MULTIVESSEL DISEASE: EXPLORING THE OPTIMAL STRATEGY FOR CORONARY REVASCULARIZATION - AKBER, S; KHAN, AS; KHAN, FR (Biological and Clinical Sciences Research Journal, 2024)
Multivessel coronary artery disease (CAD) presents a significant challenge in patients with acute coronary syndromes (ACS). Primary percutaneous coronary intervention (PCI) is a widely accepted treatment strategy for high-risk patients, including those with ST-elevation myocardial infarction (STEMI) or non-ST-elevation myocardial infarction (NSTEMI). However, whether immediate multivessel PCI or staged PCI leads to better outcomes remains an area of ongoing research. Objective: This study aims to compare the clinical outcomes between immediate multivessel PCI and staged PCI in patients with multivessel CAD undergoing primary PCI. Methods: This retrospective cohort study was conducted at a tertiary care center, collecting data from 1st March 2023, to 31st March 2024. The study included 200 patients aged 18 years and older diagnosed with ACS and multivessel disease, defined as stenosis ≥70% in at least two coronary arteries. Patients were categorized into two groups based on the PCI strategy (immediate multivessel PCI vs. staged PCI). The primary endpoint was major adverse cardiovascular events (MACE), a composite of all-cause mortality, myocardial infarction, target vessel revascularization, and stent thrombosis. Secondary outcomes included recurrent angina, heart failure requiring hospitalization, and bleeding complications. Statistical analysis was performed using SPSS version 26.0, and survival analysis was conducted using the Kaplan-Meier method. Results: MACE occurred in 48 patients (24%) during the one-year follow-up. The staged PCI group showed significantly lower MACE rates (16%) compared to the immediate PCI group (32%, p = 0.005). Recurrent angina was also less frequent in the staged PCI group (10%) compared to the immediate PCI group (18%, p = 0.046). Multivariate analysis identified diabetes mellitus (HR: 2.4, p < 0.001) and CKD (HR: 2.1, p = 0.002) as independent predictors of MACE. Conclusion: Staged PCI offers superior outcomes compared to immediate multivessel PCI in patients with multivessel CAD, particularly those with diabetes and CKD. These findings suggest that individualized revascularization strategies may improve long-term cardiovascular outcomes in high-risk populations.